Analyzing Food Prices in North Sumatra Province in 2022 – 2024 Using the Linear Regression Method - Faza, Sharfina; Firjatullah, Muhammad; Azhar, Muhammad Fauzan; Hidayatullah, Rafly Artha; Lubis, Arif Ridho (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
The food price data used was obtained from literature studies which include main food ingredients such as rice, beef, chicken, eggs, red onions, red chili pepper and cooking oil. The linear regression method is used to model the relationship between the independent variable (year) and the dependent variable (food prices), with the aim of predicting future food prices based on historical data. Although linear regression can provide fairly accurate food price estimates, improvements in prediction models can be achieved by incorporating other analysis methods such as time series analysis or machine learning. The implications of this research highlight the importance of effective policy planning to maintain food price stability and ensure sufficient food availability for the community. Future research could involve more in-depth analysis of the factors influencing food prices, as well as the development of more sophisticated prediction models to support decision-making in agriculture and food. This research aims to analyze food prices in the Northern region of Sumatra Province during the period 2022 to 2024 using the linear regression method. The results show that rice, meat, chicken meat, chicken eggs, shallots, red chilies and edible oils all increased, but only chicken meat, shallots and edible oils also experienced a decrease.